Russian Language in the Central Asia Region - K. P. Borishpolets (Vestnik MGIMO-Universiteta)
He article is devoted to the role of the Russian language in Central Asia and its development perspectives in the context of the Eurasian integration processes. Russian language has a long historical tradition in Central Asia and hasn't lost its importance even at the background of two waves of "derussification" that took place after 1991. Notwithstanding the decrease of the status, it keeps substantial public significance. During last two decades only in Turkmenistan we are witnessing the decrease in spreading of the Russian language among title population of the Central Asia region. Its positions as an active communication channel is secured not only by the social tradition, but also by the competitiveness of the Russian language education, advantages of the bilingual business, requirements of the labor migrants, HR interests and by some other pragmatic thoughts, which role within the context of Eurasian economic integration will increase. Despite the difficulties, it is too early to speak about the decrease of the Russian language in the Central Asia region. It is more likely that the institutes itself that maintain it and promoting it are at the low ebb. New scales and forms of practical work that is interested not only for Russia, but also Central Asia countries are required. Pressure on the resources of the Russian language increases the possibility of ethnic conflicts and strengthens the positions of political radicalism in Central Asia region.